(untitled) (PANGEEA, 2025)
The topic of minor mothers is essential to protect the health and well-being of young mothers and their children, to ensure access to education and economic opportunities, to combat marginalization, and to implement effective public policies that support these young women in their development. This paper aims to highlight the essential role that the social worker plays in emergency reception units (ERU) in their relationship with pregnant minors and young mothers. This vulnerable group often faces a range of socio-economic and psychological challenges, and the intervention of the social worker is crucial in assessing the needs of these patients and establishing a beneficial path forward. The presence of pregnant teenagers or young mothers in the ERU brings a series of medical, psychosocial, and legal challenges that require a sensitive and specialized approach. The social worker acts as a mediator between the minor patient, the medical team, and relevant authorities, with the role of ensuring the protection of her rights, providing counseling and emotional support, and facilitating access to appropriate social assistance services. In this context, the paper outlines the responsibilities of the social worker and the importance of collaboration with the multidisciplinary team, as well as the role of social interventions within the ERU in the reintegration process of these teenagers into the community. It analyzes the challenges faced by young mothers, including social stigma and lack of resources, and highlights effective intervention strategies such as prenatal education and the encouragement of open dialogue. Additionally, it addresses specific challenges and the need for ongoing professional training to effectively handle the delicate and complex situations encountered in daily ERU practice.